2019
DOI: 10.24840/2183-0606_007.001_0007
|View full text |Cite
|
Sign up to set email alerts
|

Identifying enablers of innovation in developed economies: A National Innovation Systems approach

Abstract: It has been recognized that innovation drives the long-run economic growth of nations and increasingly governments are placing innovation at the center of their economic growth strategies. International variation in the investment on innovation presents an opportunity to examine key enablers of innovation-driving policy choices. Countries find themselves at different stages of economic development and innovation performance and so their relative levels of innovation inputs and outputs are likely to be differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Aguilar-Barceló and Higuera-Cota (2019), Cetinguc et al (2019), Hamidi and Berrado (2018),Menna et al (2019),Natocheeva et al (2019) and Singh (2020) also indicated the importance of R&D for innovation in the studies.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Aguilar-Barceló and Higuera-Cota (2019), Cetinguc et al (2019), Hamidi and Berrado (2018),Menna et al (2019),Natocheeva et al (2019) and Singh (2020) also indicated the importance of R&D for innovation in the studies.…”
Section: Discussionmentioning
confidence: 86%
“…It is no longer expedient for economies to rely on labour-intensive industries for economic growth and job creation because such industries have moved to developing countries with lower wages and lower production costs. This makes government’s place innovative at the centre of their economic growth strategies (Menna et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as e-government has become more advanced, it has overcome the limitations of supplier-based service and strengthened its approach toward all aspects of government by using ICT technology and the Internet [31]. Many countries have been focusing on ICT investment and technology development to advance information technology of the e-government and to enhance national competitiveness [4].…”
Section: The Future Direction Of Innovative E-governmentmentioning
confidence: 99%
“…It also strengthens the government's capability of systemizing knowledge and information of the government organizations electronically and of managing government organizations efficiently [3]. In order to improve the capabilities of e-government, ICT investment and technology development have become the center of attention in making information technology develop and in enhancing national competitiveness [4].…”
Section: Introductionmentioning
confidence: 99%